Analysis of Writing Ability of Class II B Students at SDN 015 Samarinda Ulu Academic Year 2022/2023 - Hani Subakti; Inne Pelangi; Fitri Endang Srimulat (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The purpose of this study was to analyze the writing ability of students in class II B at SDN 015 Samarinda Ulu. The method was a descriptive qualitative approach. This research was conducted at SDN 015 Samarinda Ulu and it was carried out in February 2023. The data collection techniques were observation, interviews, and documentation. The instruments were observation sheets and interview sheets. The triangulation techniques were 1 homeroom teacher and 5 students of II B at SDN 015 Samarinda Ulu. The sampling technique was purposive sampling. The data analysis techniques in this study were data collection, data reduction, data presentation, and concluding. The results showed that students' writing skills were still lacking because students' abilities were at a different level. Some students experienced different obstacles, either from not being good at writing, not having space between words, and still experiencing confusion in putting letters into a sentence. Less interest also caused writing skills to tend to be less meanwhile students become less enthusiastic to learn. Furthermore, students' low motivation to write could be seen from the lacking of effort that students have.